A bead of mass slides along a stationary circular ring of radius . The ring has a friction coefficient , and the ambient gravitational acceleration is downward and parallel to the plane of the ring.
At time , the bead is at the farthest left part of the ring, with a downward speed . The experiment is run twice. For , the time at which the bead first reaches the bottom of the ring is . For , the time at which the bead first reaches the bottom of the ring is .
What is ?
Details and Assumptions (everything in SI units):
-
-
-
-
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If the radial line to the bead makes an angle θ with the downward vertical, the equations of motion of the bead are m R θ ˙ 2 = N − m g cos θ m R θ ¨ = F − m g sin θ where N and F are the normal reaction and friction force acting on the bead. Since friction is limiting while motion occurs, F = μ N . Thus we obtain the equation m R θ ¨ + m g sin θ R ( θ ¨ − μ θ ˙ 2 ) R d θ d [ 2 1 θ ˙ 2 e − 2 μ θ ] = μ ( m R θ ˙ 2 + m g cos θ ) = g ( μ cos θ − sin θ ) = g ( μ cos θ − sin θ ) e − 2 μ θ = 1 + 4 μ 2 g d θ d [ ( ( 1 − 2 μ 2 ) cos θ + 3 μ sin θ ) e − 2 μ θ ] and hence, given the initial conditions θ ˙ 2 = F μ ( θ ) = R ( 1 + 4 μ 2 ) 2 g [ ( 1 − 2 μ 2 ) cos θ + 3 μ sin θ ] + ( R 2 v 0 2 − R ( 1 + 4 μ 2 ) 6 μ g ) e − μ ( π − 2 θ ) Thus the time taken to reach the bottom is T ( μ ) = ∫ 0 2 1 π F μ ( θ ) d θ Numerical calculations give us that t 1 = T ( 0 ) = 0 . 6 2 3 2 2 5 t 2 = T ( 0 . 4 ) = 0 . 8 4 9 0 1 2 and hence t 1 t 2 = 1 . 3 6 2 2 9